Unusual case of spinal subdural empyema with ventriculitis managed conservatively with lumbar drain. Issue 2 (28th February 2022) - Wassef, Catherine; Johnson, Angelique; Stone, Jonathan
Abstract : It has long been believed that spinal subdural empyemas (SDEs) with neurological symptoms result in death if operative intervention is not performed. We present a case of addressing an extensive spinal SDE with a minimally invasive procedure: a bedside lumbar drain. Our patient is a 67-year-old man with medical history significant for type I diabetes who presented 2 weeks after a right shoulder steroid injection with septic arthritis. An MRI was obtained for back pain which revealed spinal SDE from the cervical to lumbosacral spine. Given patient's acute sepsis, haemodynamic instability, and extent of empyema, we placed a lumbar drain for decompression. The patient had a prolonged complicated hospital course. Imaging 2 months later revealed interval decrease in the spinal SDE. Although this severe septic event left the patient with significant deficits, he was able to return to ambulation without surgical intervention.